Predicting Greek Cypriot children's reading and spelling from morphological and dialect awareness - Pittas, E (2011)
The aim of this longitudinal study was to examine the contribution of phonological, morphological and dialect awareness to the prediction of reading and spelling in a Greek bi-dialectal setting. The target group (N=404) consisted of children, aged 6 to 9 years at the start of the project, who learn literacy in Cyprus, where a dialect is spoken in certain contexts but where Standard Modern Greek is also widely used. At present there are few studies with Greek Cypriot children on how phonological, morphological and dialect awareness relates to reading and spelling. Because there are no standardised measures of phonological, morphological and dialect awareness with Greek Cypriot children, measures of these factors were developed during the pilot study and their internal consistency was assessed. With the larger sample the measures were validated by examining their construct validity. The first wave of data collection showed that morphological and dialect awareness make unique contribution to the prediction of reading and spelling in Greek. The second wave of data collection showed that the measures of morphological and dialect awareness predicted performance in reading and spelling eight months later, even partialling out grade level, estimation of verbal intelligence and initial scores in reading and spelling. A model with dialect awareness as a mediator between phonological and morphological awareness and reading and spelling fitted the data better than a model with phonological or morphological awareness as mediators, and hence, phonological awareness and morphological awareness help children to become aware of the differences between their dialect and the standard variety, and dialect awareness in turn facilitates reading and spelling. Cross-lagged correlations showed that the more experience children have with reading and spelling, the more likely they are to develop morphological and dialect awareness. This study makes theoretical, empirical and practical educational contributions. The established mediational model contributes to the theoretical knowledge of the connection between dialect awareness and phonological and morphological awareness and reading and spelling while the longitudinal study contributes to theory the long term relation of morphological and dialect awareness with reading and spelling in Greek. Empirically, the study established the plausibility of a causal link between morphological and dialect awareness and reading and spelling, which must be tested in further research using intervention methods. In practice, this study contributes valid measures for assessing morphological and dialect awareness in the Greek Cypriot setting.